Sustainable Material : Used Wood As Building Material - Susanto, Dalhar; Widyarko, Widyarko (International Series on Interdisciplinary Science and Technology, 2017)
Abstract–Wood consumption as building material and component in Indonesia is still considerably high. This affects forest destruction, in a way that most of the wood production still roots from wood forests. Hence, the demand of these woods better be supplied from other source, one of them is through using used woods. Used wood utilization in building construction is an application of reuse and recycle strategy in sustainable material concept. Due to the assumption among the people that used woods have low performance its utilization is nowadays limited. This paper addresses the result of research and laboratory test on a range of used wood samples collected from Jakarta great area (Jabodetabek), consist of 5 technical parameters: water content, density, compressive strength, flexure strength, and tension strength. The research proves that based on certain parameters, used woods perfom technical capacity as good as – or even better than – newly produced woods. Keyword – sustainable, material, used wood